Innovative Exploration of the Connotation and Education and Training Practice Path of Outstanding Pharmaceutical Engineers - Chen, Juan; Ji, Yingying; Qian, Hongliang; Li, Jiayu; Sun, Chunmeng; Wang, Xinran; Jiang, Cheng (Indian Journal of Pharmaceutical Education and Research)
Objectives: China is on the way to improving the education and training of outstanding pharmaceutical engineers. Still, the training of pharmaceutical engineers cannot meet the needs of innovative drug development and transformation research. So, it is worth sorting out the existing problems to improve the professional identity, enhancing professional confidence and the quality of the training. Materials and Methods: First, using questionnaires and interviews to understand the current situation of the education of engineers with excellence; second, collecting information on the current trouble and demands from those students in the learning process; finally, analyzing the problems in the education of engineers with excellence. Results: The current training concept is still stuck in the scientific paradigm, so there is a lack of training in scientific thinking, “discipline logic” and the big engineering system. The sense of professional identity still needs to be improved because of the present failure to use diversified educational subjects. Also, the mechanism of integration of industry and education needs to be further strengthened. Conclusion: The design of industry-education integration should be optimized to “full-cycle, developed occupation and full openness” to enhance recent graduates’ occupational adaptability. Using “new drug research and development” as the guidance to create a four-chain model of industry-education integration which is composed of an “innovation chain”, “education chain”, “industry chain” and “talent chain”. Using “coordination, incentives and evaluation” as the standard to develop a long-term mechanism for the fusion of industry and education.
Keywords: Outstanding pharmaceutical engineer; Connotation; Practical path; China; Occupational competency.